A phenomenological analysis on infertility in Mexican women living in the United States of America - Brito, Janet (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2018)
Infertility, or the inability to conceive, after 12 or more months of unprotected sexual intercourse (American Society for Reproductive Medicine, 2008) affects women worldwide. The literature on the impact of infertility for Mexican women living in the U.S. is sparse. This phenomenological study examined the experiences of five Mexican women with infertility, ages 30-39, living in Queens, New York. Data collection comprised of conducting interviews in Spanish. Thematic results showed significant emotional distress, stigma, social, familial, and personal pressures to conceive, positive marital relations, body and sexual concerns, the use of spiritual coping approaches and natural solutions to infertility. Although the study is not meant to be generalizable, these findings serve to provide a cultural context of how Mexican women experience infertility.